The Characteristics and Influencing Factors of Nonsuicidal Self-Injury of Adolescents With Depressive Disorder in China: A Meta-analysis - Niu, Hui-Ming; Zhang, Zi-Ming; Mu, Xiao-Mei; Zhao, Hai-Jing (The journal of nervous and mental disease, 2023)
This study is a systematic review of characteristics and influencing factors of nonsuicidal self-injury behavior among adolescents with depressive disorder in China. PubMed, CNKI, WanFang Database, and VIP were searched for studies. Meta-analysis was performed using RevMan 5.1 software. Nineteen studies involving 707 subjects were included in the meta-analysis. Age, gender, only child or not, and residence were included in the analysis, of which age ( I2 = 0%, p = 0.42) and residence ( I2 = 0%, p = 0.84) were analyzed by fixed-effects model; gender ( I2 = 75%, p = 0.003) and only child or not ( I2 = 50%, p = 0.140) were analyzed by random-effects model. The evidence shows that, according to the common self-injury mode and location, the nonsuicidal self-injury behavior of young people with depressive disorder aged 15-18 years is paid attention to and guided, so as to achieve early detection and early diagnosis and treatment, and reduce the occurrence of serious harm.